2018
DOI: 10.1038/s42004-018-0025-z
|View full text |Cite
|
Sign up to set email alerts
|

Differential inhibition of metabolite amyloid formation by generic fibrillation-modifying polyphenols

Abstract: The formation of ordered amyloid fibrils by proteins and polypeptides is associated with human disorders. A recent extension of the amyloidogenic building block family includes several small metabolites, which form assemblies with structural and functional similarities to well-established amyloids. Here we investigate whether generic amyloid polyphenolic inhibitors can also restrict the formation of metabolite fibrils. We reveal that epigallocatechin gallate and tannic acid inhibit amyloid-like fibrillation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 61 publications
(91 citation statements)
references
References 66 publications
4
87
0
Order By: Relevance
“…While previous research has shown that tannic acid can reduce the production of neuroinflammatory factors such as ROS, NO and TNF-α from LPS-treated microglia via the suppression of the NF-κB pathway, our results show that tannic acid only reduces intracellular ROS production but does not have an appreciable effect on the other two markers (Figures 5A-D; Wu et al, 2019). This could potentially suggest that the rate at which tannic acid associates with αSYN is much faster than its interaction with other signaling molecules involved in the pathway (Shaham-Niv et al, 2018). The only major inflammatory biomarker that was not appreciably modulated by the [FAA:TA] NPs was IL-6 production from LPSprimed microglia ( Figure 5D).…”
Section: Discussionmentioning
confidence: 69%
“…While previous research has shown that tannic acid can reduce the production of neuroinflammatory factors such as ROS, NO and TNF-α from LPS-treated microglia via the suppression of the NF-κB pathway, our results show that tannic acid only reduces intracellular ROS production but does not have an appreciable effect on the other two markers (Figures 5A-D; Wu et al, 2019). This could potentially suggest that the rate at which tannic acid associates with αSYN is much faster than its interaction with other signaling molecules involved in the pathway (Shaham-Niv et al, 2018). The only major inflammatory biomarker that was not appreciably modulated by the [FAA:TA] NPs was IL-6 production from LPSprimed microglia ( Figure 5D).…”
Section: Discussionmentioning
confidence: 69%
“…Tannic acid (TA) and epigallocatechin gallate (EGCG), are two polyphenolic compounds previously shown to inhibit the self-assembly of proteinaceous amyloids [ 27 , 28 ] and recently demonstrated, using time-dependent ThT fluorescence assay, to hinder the Tyr self-assembly process [ 29 ]. Pre-treatment of the Tyr solution with either of the polyphenols hindered immune-recognition ( Figure 2 A-IV–V).…”
Section: Resultsmentioning
confidence: 99%
“…Insoluble brillar polypeptide structures appear as a result of a misfolding process in numerous proteins or peptides and accompany the amyloid aggregation process. [1][2][3][4][5][6] The most spectacular structures of this type are linked to the development of fatal neurodegenerative disorders such as Alzheimer's disease, 7,8 Icelandic type amyloidosis 9,10 or Creutzfeldt-Jakob disease. 11,12 The latter belongs to the group of diseases called transmissible spongiform encephalopathies (TSE) in which a misfolding of human prion protein (PrP) is responsible for the formation of brillar aggregates in the brain.…”
Section: Introductionmentioning
confidence: 99%